2007
DOI: 10.2143/ac.62.2.2020233
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin in patients with acute coronary syndrome

Abstract: In conclusion, levels of hsCRP and procalcitonin are increased in patients with ACS but failed to correlate with severity of coronary disease and early prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…hs-CRP and IL-6, as mediators and markers of atherosclerotic thrombosis, play an important role in the development of CVD [28]. The levels of hs-CRP and IL-6 in the CVD group were higher than those in the non-CVD group, consistent with the findings in previous studies [29, 30]. This suggested that the levels of hs-CRP and IL-6 were elevated, the population may be present in the pre-onset phase of CVD.…”
Section: Discussionsupporting
confidence: 90%
“…hs-CRP and IL-6, as mediators and markers of atherosclerotic thrombosis, play an important role in the development of CVD [28]. The levels of hs-CRP and IL-6 in the CVD group were higher than those in the non-CVD group, consistent with the findings in previous studies [29, 30]. This suggested that the levels of hs-CRP and IL-6 were elevated, the population may be present in the pre-onset phase of CVD.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Şentürk et al identified elevated PCT and cTn levels in those with high TVCAD and that it was simultaneously correlated with mortality [7]. In our study, groups with high PCT and cTn had higher mortality, TVCAD, and complications.…”
Section: Discussionsupporting
confidence: 66%
“…13,14,30 By contrast, other previous reports state that myocardial infarction per se is associated with a significant release of PCT. 31,32 Moreover, PCT was proposed as a sensitive marker of myocardial damage as well as being associated with left ventricular remodeling and worse clinical outcome following infarction. 15,16,32 Taken together, these limited and controversial previous data cannot clarify the clinical significance of PCT in the setting of acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%